Epigenetic modifications in cardiac fibrosis: recent evidence of new pharmacological targets - Pérez, Marian; Gómez, Mónica; Castellar-López, Jairo; Araos, Patricio; Mendoza-Torres, Evelyn; Bolívar, Samir (Frontiers in Molecular Biosciences, 2025)
Cardiac fibrosis (CF) is characterized by the excessive deposition of collagen types I (COI I) and III (COI III), primarily mediated by cardiac fibroblasts (CFB). Recent advances in epigenetic research have enhanced our understanding of the molecular mechanisms underlying CF and have facilitated the identification of novel therapeutic strategies targeting key proteins and signaling pathways involved in its progression. Epigenetic modifications, including DNA methylation, histone modifications, and non-coding RNAs (ncRNAs), are structural and chemical alterations that regulate gene expression and cellular responses without changing the DNA sequence. Investigating the role of epigenetic enzymes in CF may reveal promising pharmacological targets. This review summarizes current evidence on epigenetic modifications implicated in CF and discusses their potential as therapeutic targets for modulating this pathological process.